26th Palc Day 1 Part 49 (Βιβλιοθήκη & Κέντρο Πληροφόρησης ΕΜΠ, 2021)
: Ευχαριστούμε πολύ. Ευχαριστούμε πολύ. Είστε έτοιμοι για εσάς? Ναι, ευχαριστούμε, κυρία Αναστασία. Ευχαριστούμε και ευχαριστούμε για να μας περιμένετε σήμερα, όλοι τους συγγραφούς μας στο Healink και στο Pal Conference στην Ελλάδα. Ευχαριστούμε πολύ που μας συμμετέχετε. Είμαι εδώ με τον συγγραφό μου, τον Jennifer Fong, που είναι... Γεια, Jennifer. Είναι η διευθυντρική... Είναι η διευθυντρική του IEEE Education Products. Είμαι να σας μιλήσω σήμερα από το σπίτι μου, στο Chicago, στην Ελλάδα, και, χωρίς περισσότερο, εδώ είναι μια γρήγορη παρουσία για το IEEE E-Learning και το Internet of Things. Ένα γρήγορο παράδειγμα για το IEEE. Ακόμα και με το Pal Conference, πιστεύετε εμείς ως επαγγελματικοί, σημαντικές γερμανικές, συγγραφές και εργασιακές στανδέρες, το IEEE είναι πραγματικά μια σχολική κοινότητα, μια κοινότητα, που έχει σχεδόν 420.000 ανθρώπους, όχι μόνο άνθρωποι στην ακαδημία, σχολείες και φακοί, αλλά επίσης και εργασιακοί, από όλες τις τεχνολογίες του IEEE, είτε είναι το συγκεκριμένο, το διευθυντρικό, τη μηχανική τεχνολογία, τις διευθυντρικές, και η σκέψη μας είναι η διευθυντρική τεχνολογία, για το διευθυντρικό της ανθρωπότητας, και το κάνουμε με πολλές πολύ συγκεκριμένες διευθυντρικές προγράμματα. Αυτή είναι η διευθυντρική τεχνολογία, που βλέπουμε στο website of Mumbai. IEEE, we organize our members on a country by country basis, including in Greece. We organize industry conferences where cutting edge technologies are first presented, and we develop industry standards and all of that material, including e-learning is found on the IEEE Explore digital library. Thank you Healink for including us today. And back when the pandemic was just starting, this crazy year of the pandemic, IEEE made many of the courses of the IEEE e-learning library available throughout the world. And for free, because we wanted to assist academics who were making that transition from live education, traditional education, to remote education, or e-learning. And interesting, when we looked at the statistics after the program was completed, we found that Greece made excellent use of all of the IEEE courses. And that's very much thanks to the administrators at Healink, who made it available to all of the Greek universities. So after countries like India and the United States and China, who you would imagine would be very voracious users of IEEE, Greece was the number one country, more than any other country in Europe. So because of that data, and your interest in e-learning, we wanted to take just a brief couple of minutes to tell you about IEEE e-learning programs. They're not currently available through Healink, but maybe we could talk about them if there's an opportunity to make that available to students and faculty at universities in Greece. So the IEEE e-learning program is hundreds of hours of courses in IEEE technologies, and that's found on IEEE Explore, or the IEEE Learning Network. And it's all of the key technologies that we talked about, communications, computing, robotics. And we stay at the forefront of technology, both with foundational courses, but also with cutting-edge material that's all peer-reviewed to make that available, either as part of a course syllabus, or for a student studying on her own, just to familiarize herself with this kind of material. So here you see courses on blockchain and healthcare, 5G networks, finite element method for photonics, and also a course on standard, standard 1547, related to the smart grid, connected distributed energy resources. But wait, there's more. Autonomous vehicles, that's an Internet of Things application. We have a course program in that. Digital transformation, a key area that's a very hot topic throughout the world, including machine learning and artificial intelligence standards. So this is the kind of peer-reviewed material that Greece has made very good use of, and perhaps you might consider working with Healink and bringing that to the community in the years to come. Another program I just wanted to do a quick mention of is IEEE English for Technical Professionals. This program is interesting because when I travel in Greece and I enjoy doing so, everyone speaks English very well. So speaking English has come second nature to Greeks. Clearly, English is the lingua franca of Europe, and any international or European project will require working in English. But of course, working in English is different from having a romantic partner in English or just spending or traveling in English. So this focuses on engineering and project management with a focus on improving people's English skills so they can be an effective manager in the English language. So again, engineering concepts and complexity in English, looking at cause and effect and calls for proposal, responding in English, and the tense in the language about future tense for technical work, all in English. Again, our Greek colleagues are excellent English speakers, but this will hone their skills, make it more precise so they're comfortable functioning in the European context, in the work context, in English. So that's English for technical professionals. It's 14 hours of coursework, and we think that's worth discussing with the Healink team to bring to our colleagues in Greece. One last program I wanted to mention. Perhaps it's outside of the scope of Healink, I'm not sure, and perhaps my colleagues there can give me some advice, but there's a long, a very historic university in the United States, Rutgers University, that is a leading university in business education, and we found that engineers after they're out of their engineering education for three, four, five years, they then ascend to a leadership position, and they grow within a ministry or with a European project or within an international corporation. They're great with engineering, but they're less knowledgeable about business and how large organizations work. They're less familiar with accounting, marketing, finance. So in this 12-week program with live professors from Rutgers University available, they learn about all these key modules, 12 modules in all, and this is a program that has a capstone project at the end of it, which could be tailored to a Greek economic development project, a European project, and we think it's very interesting, again, for early career engineers. So I'm open to advice and comments if there's a way to bring this exciting program to my colleagues in Greece. So let's speak to Jennifer Fang, who makes all of these programs possible. Ms. Fang is the director of IEEE Educational Products, and in earlier life she was a classroom teacher and structural designer, who now is the head of IEEE Product Development and Sales and Marketing for our education programs. And her team works with top technical experts from around the world to develop courses, like I showed you, for the IEEE Learning Library, a collection of hundreds of online courses. So Jennifer is going to speak to us today about the Internet of Things, and I turn the conversation over to my colleague, Jennifer Fang. Great, very much, Paul, and hello everyone. Thank you for being here today. I know this is your last presentation of the day, so we thank you for hanging in there with us today. Hopefully you'll find this interesting. I want to share with you a little bit about the Internet of Things, how it is fueling digital transformation as organizations seek to optimize internal operations and boost revenue streams. And today what I want to talk to you about is what are some of the benefits that organizations experience by embracing digital transformation, and then take a look at some of the ways the Internet of Things is being used for digital transformations in the healthcare, industrial manufacturing, and power and energy industries. Now, I am going to share up front. I am an education person, so I'm not an expert in all the things in these fields. However, we at IEEE have a number of subject matter experts from around the globe who are on the leading edge of the Internet of Things and digital transformation. At the end of the presentation, I'm going to share with you some of the courses from IEEE where you can learn more about some of these topics and grow knowledge about this very important field. So, let's start with a definition. Salesforce defines digital transformation as the process of using digital technologies to create new or modify existing business processes, culture, and customer experiences to meet changing business and market requirements. The reimagining of business in the digital age is digital transformation. According to research, market pressure is the major digital transformation driver. Even established market leaders struggle to compete with tech-enabled agile startups. And digital transformation is the only way to future proof a business and survive in times of tech disruption. This market pressure is created by a combination of evolving customer expectations, rising costs, and an ever-changing business and regulatory environment. Strategic digital transformation starts with the challenges that a business needs to address, which can be different depending on industry, but there are also some consistencies that all businesses need to address. And an organization might be seeking to bring products to market faster, better regulate the flow of energy based on shipping demands, better utilize manufacturing resources while performing predictive maintenance, or use customer data to inform product development while providing more customized customer experiences. So, there are multiple ways that a business can be transformed when using IoT solutions. Here are some of the benefits that businesses experience when using the Internet of Things to drive digital transformation. First of all, opening up new business opportunities. By using data generated by IoT devices, businesses can better understand their customers' needs and adjust their product offerings accordingly as well as introduce new products and services to reach a broader audience. Also delivering meaningful, tailored customer experiences. By capitalizing on new sources of customer data, such as IoT devices, businesses can gain deeper insight into customer behavior and tailor their customer experience accordingly through advanced personalization and increased accessibility. Boosting business efficiency. Combining rich data insights and autonomous sensors, IoT has the potential to increase business efficiency through process automation. There are dozens of important business processes that can be streamlined, including inventory management, logistics, security, energy management, and a lot more. Reducing operating costs. That is so important, and process automation will inevitably lead to cost savings and allow organizations to use their resources wisely. For example, IoT energy solutions can help an organization better manage your utility consumption and eliminate waste. This approach can be applied to heating, ventilation, air conditioning systems, lighting, water supply, the list goes on. And of course, improving employee productivity. Just like cloud and mobile technologies, IoT can help organizations empower staff by offering better agility and making business systems easily accessible anywhere at any time. So smart sensors can keep employees connected at all times and deliver real-time insights for better productivity. And enterprises that are engaged in big digital transformation initiatives, which involve using digital technology to overhaul the fundamentals of how they do business, are deploying IoT solutions to optimize their internal operations, boost revenue streams, and support their efforts to become more nimble, agile, and efficient. So some of the main uses for enterprise IoT today revolve around asset management, tracking, and tracing. For example, minimizing equipment downtime. You can use IoT to help fix or even prevent failures in equipment such as heating, ventilation, and air conditioning systems, agricultural machinery, and commercial boilers. IoT devices enable predictive maintenance, alerting the system when equipment is not working optimally, and allowing the organization to address these issues before they become system failures that can cause business interruptions. Optimizing replenishment revenues. Asset management can be positively impacted by using IoT. Enterprises with offerings that include something that needs regular replenishment or replacement, it could be anything from coffee bean supplies to HVAC filters, you can create IoT solutions to reduce waste and lower costs. Controlling inventory costs. You can create IoT solutions to track inventory and monitor stock levels remotely, continuously, and in real time. IoT-based inventory management systems can not only alert companies when inventory levels are getting low, but also fill that stock automatically. And reducing risk and streamlining compliance. Being out of compliance, whether that involves a shipment of frozen meat at a grocery store or blood samples to a medical lab, that can put people's health and safety at risk. And it can be very expensive. So you can use IoT devices to track and trace perishable goods for improved risk management and compliance. Let's take a look at a couple of industry verticals where IoT is very important. And these are some of the things that we look at in our courses on IoT and digital transformation at IEEE. Given the realities of the pandemic right now, it seems timely to look at the healthcare industry and how IoT and digital transformation can help streamline and improve health outcomes. First, electronic health records can make it easier to keep track of patient health, whether it be an individual's health or using that data in an anonymized form to track the health of the population. By making the data easily accessible in electronic form, patients can easily take their health records with them wherever they need to receive care. And those records can be included when tracking the progress of the pandemic and other health emergencies. Of course, with those health records comes the very real issue of data privacy. It's important for healthcare providers to ensure that these electronic healthcare records are handled according to the law. And there are certainly data privacy implications with all of the data collected by IoT devices. There are also other digital advances in healthcare. There are wireless health monitoring devices, and these Internet of Things devices allow patients to keep track of their own health. And some also alert physicians or family members if there is a problem. There are mobile apps on people's phones that can help them track food intake, exercise, nudge them to take healthy actions, and more. And these apps help individuals track their health choices daily, which makes them more aware and may help health leaders become aware of small problems before they become bigger in populations. But what happens when there is an overabundance of data, especially in a global health emergency like the pandemic? Well, that's where artificial intelligence comes in. The fact is that Internet of Things devices are producing far more data than any human can process in a reasonable amount of time ever. And especially in healthcare, minutes matter. By using artificial intelligence to look for trends and advances, healthcare can be improved for both individual patients as well as populations. And let's also consider contact tracing, such an important activity in the midst of this pandemic. How can we get the word out quickly when someone has been exposed? Well, mobile apps that alert people when they have been in the vicinity of an outbreak while also tracking the spread means that we can use technology to slow the spread and hopefully end the pandemic sooner rather than later. The use of IoT for digital transformation, however, is not just limited to healthcare. Industrial manufacturing is also speeding up production while maintaining quality through the use of robots, sensors, and other IoT devices that perform, track, and report on millions of steps in the manufacturing process daily. For example, Sanmina, a producer of integrated manufacturing equipment, has leveraged connected sensors and the cloud to improve the performance of its factories while also addressing IoT data security challenges. In 2016, Sanmina wanted to increase the overall equipment effectiveness known as OEE of its production equipment at its factory in Ireland. OEE is an industry standard metric of how well a manufacturing facility is used compared with its full potential during the periods when it's scheduled to run. And Sanmina wanted the factory's manufacturing lines to be producing one unit every second. That's pretty crazy when you think about it. But they've used multiple technologies that work in tandem that manage everything from environment to humidity, cloud-based artificial intelligence platforms, all kinds of systems that work together. And they rely on computerized maintenance management systems that use data collected from IoT devices that are mounted on assets to schedule maintenance and calibration of machines. It also gives them real time views and replenishment of raw materials to ensure that there are no delays in material supply. And then automated vehicles deliver those supplies to the warehouse floor. As a result of the deployments, the factory increased its OEE of production equipment and manufacturing lines and achieved seamless replenishment of raw materials on its shop floor, thereby eliminating delays. And this has been such a success for Sanmina that they have now added similar installations in factories around the world. In fact, to date, they have connected 25,000 pieces of manufacturing equipment at different sites around the world, allowing software to collect data directly from machines, control production, and proactively request engineering intervention when required. One of the things that's interesting though, they say that their biggest challenge with IoT is security. While the issue of securing the data that is collected is an obvious challenge, IoT devices can become the gateway to gain entry into corporate networks. This is in some ways a larger concern and needs sophisticated network configurations as well as authentication technologies to deter hackers from gaining access. And then some other challenges include the ability to ingest and process high volumes of streaming data so they can make near real time decisions on the shop floor. And this is addressed through a combination of edge computing, by the way we also have course programs on edge computing, and sophisticated data compression and transmission techniques. And one more industry use case I just wanted to take a look at real quick is power and energy. Another industry that's looking into incorporating IoT into digital transformations is this industry. According to Gartner, utilities will be the highest user of IoT endpoints. And it was projected in 2022 to increase 17%. It is important for large energy companies to embrace IoT resources to stay competitive against startup disruptors in this market. Gartner says that electricity smart metering both residential and commercial will boost the adoption of IoT among utilities. And another example is that power and energy companies monitor transformers and the grid through a vast IoT network of sensors. Georgia Power, for example, has significantly reduced grid downtime by identifying potential failures in transformers before they happen. It's important that energy companies realize the promise of digital transformation at scale on a global basis. It matters to the world. Over the next two to three decades, more than 5 billion people across the developing world will seek a path out of poverty. And unlocking the magnitude of energy resources required to improve their lives in a way that doesn't choke the environment cannot be done without the power of digital to improve efficiency and manage complexity. So, by now it should be clear that the power of IoT in digital transformation centers around the data produced. When it's applied properly, IoT technology collects source data from the physical world and converts it into useful information for the company. And this data can be processed either in the cloud or on the edge of the network with edge computing. But in order to use that data effectively, you need a data strategy. The amount of data that Internet of Things devices that devices generate can be overwhelming. And there are numerous considerations when it comes to this data, including how will this data be processed and used to make business decisions? Where will the data be secured? How will it be secured? And is some data private and bound by data privacy regulations? These are some of the questions that we are actually exploring in a new machine learning course that we are producing right now that talks about some of the business decisions that need to be made when you are working with such a large amount of data. I'm going to just very quickly show you these are some of the course programs that we have coming either available today or coming soon from IEEE. These are all available online, can be taken from anywhere in the world on any mobile-enabled device. But we have courses on the IEEE Guide to the Internet of Things that has eight courses including some specifically around healthcare. We have a program on the introduction to edge computing. Edge computing is so important to reduce latency in Internet of Things devices because the data rather than being sent all the way to the cloud is processed at the edge of the network. Cybersecurity tools for today's environment. When we have all this data, we have to protect it. And so this program gives you some of the basics of cybersecurity. And finally, we have a program coming out in 2021 on digital transformation and exploring a lot of the issues related to this. And so with that, I will wrap it up. I know we don't have time for questions today, but I just want to thank you all for your time today, and I hope you found this interesting. It's a fascinating topic. Thank you. Thank you very much, Paul Kalik and Jennifer Fong for your presentations. They were very, very interesting. Unfortunately, we don't have time for any questions, but your presentations will be available on the conference website. And we also have the I3Clip booth on the website on the sponsor's venue. So if our audience and our participants want to find any further information or any contact information to reach you, they can find it there. Yes. We'd like to thank you again for your presentations, and I hope to see you at the next conference under other circumstances. Definitely. Absolutely. Thank you very much. Bye-bye. Thank you, Ms. Anastasia. Thank you, Healink. Thanks, everybody. Bye-bye. Thank you. Bye-bye.